Nanotubos de carbono e óxido de grafeno para a remoção de metais dissolvidos das águas contaminadas - Daniel Andrés Grajales Ruiz (2022)
One of the most pressing global concerns is the availability of clean water. Large-scale human, industrial and agricultural activities, as well as disasters such as the rupture of dams in Brumadinho and Mariana, have contaminated water with metals. One of the alternatives for the process of adsorption of metals is the use of carbonaceous nanomaterials. In this work, it was proposed the use of carbon nanotubes and graphene oxide to remove metals from the water source and give an alternative proposal to the study of a population solution focusing on the metallic ions Pb2+, Fe3+, Al3+ and Mn2+. Technological prospecting made it possible to identify the impact and scientific and technological relevance of the use and development of carbonaceous nanomaterials in the area of environmental remediation, in addition to identifying the TRL 3 maturity level according to the scale proposed by the Technische Universitat Berlin for the chemical industry. In the present study, 6 carbon nanomaterials were used, highlighting carbon nanotubes and graphene oxide with a high degree of functionalization. The materials were physicochemically characterized by measurements of particle size and Zeta potential, surface area, thermogravimetry, infrared absorption spectroscopy - FTIR, Raman spectroscopy, transmission and scanning microscopy TEM and SEM and X-ray fluorescence by total reflection - TXRF. Preliminary analysis of adsorption of metals in batch allowed the selection of multi-layer carbon nanotubes with oxidation treatment for 50 minutes (MWCNT-O50), due to having presented the best performance among all carbon nanomaterials studied, with 56% of adsorption of Fe3+ and the 65% of adsorption of Pb2+ according to the readings made by atomic absorption. During the proof of concept of MWCNT-O50 was performed using Rio Doce water enriched with the metals of interest and found adsorption of 89% of Pb2+ ions, 66% of Fe3+ ions, 36% of Mn2+ ions from the aqueous matrix The analysis of the metallic ions mixed in the proposed matrix showed a decrease in the adsorption of metals, being 72% in the case of the Pb2+ ion, 53% of the Fe3+ ion and 12% of the Mn2+ ion. The previous results indicate the potential use of MWCNT-O50 for the removal of Pb2+ ions and Fe3+ ions from the matrices, presenting themselves as versatile materials alternatives with a promising future in the area of water treatment.